On establishing coreference in Left Dislocation constructions - Oosthuizen, Johan (Stellenbosch Papers in Linguistics Plus, 2016)
The phenomenon of left dislocation (LD) has received relatively little attention in the generative literature. In Government & Binding theory and early versions of Minimalist Syntax, the left-dislocated expression is conventionally taken to be base-generated in its sentence-initial surface position and the resumptive pronoun in some other position in the structure. The establishment of an (obligatory) coreferential relationship between these expressions is usually ascribed to a special binding mechanism, A-bar binding, though this issue is seldom explicitly addressed in LD studies. The aim of this paper is to present, in broad outline, an alternative analysis of LD constructions, one that incorporates the core hypotheses of the nominal shell analysis of coreferential constructions put forward by Oosthuizen (2013a,b). On this analysis, the resumptive pronoun and the referring expression that is to serve as its antecedent are base-generated in a nominal shell structure which is headed by a presentational focus light noun, a functional category belonging to a natural class of identificational elements. The coreferential relationship between the two expressions is established within this structure by means of phi-feature valuation. The antecedent is subsequently raised into the left-periphery of the sentence, where it surfaces as the left-dislocated expression. It is claimed that such an analysis can account for the phenomenon of obligatory coreferentiality in LD constructions in terms of formal devices that are either already provided by or compatible with the basic assumptions and concepts of Minimalist Syntax. A tentative proposal is also put forward to account for the word order in LD constructions, specifically for the fact that left-dislocation does not bring about (surface) subject-verb inversion in V2 languages such as Afrikaans.